THE MANAGEMENT SUBSIDIARIES: CORPORATE GOVERNANCE MECHANISMS IN GROUP OF COMPANIES - A. K. Tatulyan (Модернизация, инновация, развитие, 2016)
Many holdings in the process of converting its organizational structure to face several new problems, which reduce the overall efficiency of the management of its group of companies. Most often these problems are related to the control activities of subsidiaries. Due to the large number of organizations in the group of companies the Supervisory Board has no possibility to monitor all the activities of its sub-sidiaries, as a result of which most of these "daughters" more freedom and opportunity to conduct their activities without agreeing it with top management. Group of companies or integrated structures imply a close interaction between companies and coordination of their activities in the moment and end-to-end operational control. The main study is how the parent organization may be based on legitimate mechanisms to manage the activities of the subsidiary. The article is devoted to the interaction between subsidiaries and the parent organization in the group companies. It also discusses a variety of mecha-nisms through which the parent organization may influence the decisions made by subsidiaries. There is a very actual problem of management and control over the activities of subsidiaries and affiliates group companies that have a well developed organizational structure, a large number of subsidiaries and lead-ing the activities of several types. These mechanisms have already proven international practice and are promising in terms of adaptation to the management structure of the Russian groups of companies that will allow you to create the best conditions for conducting control activities of subsidiaries. The article describes some of the most common tools for the management of subsidiaries, for example is the direct involvement of senior management or even the owners of parent organization in the work of the Board of Directors of the subsidiary. The article discusses the contradictions that arise in the organization of the procedure of control of subsidiaries, and the effectiveness of corporate governance mechanisms in group of companies.